Modeling the effect of temperature and notch root radius on fracture toughness - Deng, Yong; Zhang, Chao; Shao, Jiaxing; Li, Weiguo (Frontiers in Materials, 2022)
In this work, a physics-based analytical model without any fitting parameters for fracture toughness depending on temperature was proposed. The quantitative relationship between fracture toughness, melting point, Young’s modulus, Poisson’s ratio, and temperature was established. Furthermore, the effect of notch root radius on fracture toughness was investigated, and then we developed a simple theoretical model to characterize the combined effect of temperature and notch root radius on the fracture toughness. Satisfactory agreement between the available experimental measurements and our model predictions was achieved. This study not only advances our in-depth understanding of the quantitative relationship between the temperature and fracture toughness but also provides a powerful and convenient tool to predict the temperature-dependent fracture toughness at different notch root radius.